The Role of the Use of IoT (Internet of Things) Microcontrollers in the Electronics vocational education sector in Practicum Learning - Wahyudi; Muhammad Yahya (Program Studi Teknik Komputer, 2023)
The Internet of Things (IoT) has emerged as a transformative force in various industries, and its application in the field of electronics education has the potential to revolutionize practical learning experiences. This research explores the important role of IoT microcontrollers in the vocational education sector, particularly in electronics, to enhance hands-on learning during practical sessions. This research investigates the integration of IoT microcontrollers into the curriculum of electronics vocational education programs, aiming to assess their impact on student engagement, skill development, and overall learning outcomes. Through a combination of qualitative and quantitative research methods, this study evaluates the effectiveness of incorporating IoT microcontrollers in practical exercises, comparing traditional methods with IoT-enhanced approaches. The findings of this study contribute valuable insights in the optimization of practical learning experiences in electronics vocational education.